Unlocking Coban Binangun's Tourism Potential: Enhancing Village Hospitality with Plintahan Destination Branding Profile: Membuka Potensi Pariwisata Coban Binangun: Meningkatkan Keramahtamahan Desa dengan Profil Branding Destinasi Plintahan - Hatuwe, Razif Zulvikar; Bakta , Nabila Ayu; Rahmawati, Indah Agustinah; Putri, Adelia Kharisma; Wardani, Dwi Sukma; Dijaya, Rohman (International Consortium of Education and Culture Research Studies, 2023)
The aim of this service is to increase Coban Binangun's tourism potential through an attractive destination branding profile that focuses on natural attractions, culture and village hospitality. Apart from that, this service also encourages local communities to contribute to tourism development by emphasizing their hospitality and active involvement in tourist services. This service method includes tourism potential studies, which include conducting comprehensive research on the natural and cultural potential of Coban Binangun as well as assessing attractions that can be included in the destination branding profile. The hospitality training provides training to local communities about tourism services, hospitality, and how to help tourists have a good experience. The result of this service is increased public awareness and understanding of the benefits of